The impact of a patient-directed activity program on functional outcomes and activity participation after stroke during inpatient rehabilitation—a randomized controlled trial. (April 2020) - Swank, Chad; Trammell, Molly; Callender, Librada; Bennett, Monica; Patterson, Kara; Gillespie, Jaime; Kapoor, Priyanka; Driver, Simon
Objective: Individuals post stroke are inactive, even during rehabilitation, contributing to ongoing disability and risk of secondary health conditions. Our aims were to (1) conduct a randomized controlled trial to examine the efficacy of a "Patient-Directed Activity Program" on functional outcomes in people post stroke during inpatient rehabilitation and (2) examine differences three months post inpatient rehabilitation discharge. Design: Randomized control trial. Setting: Inpatient rehabilitation facility. Subjects: Patients admitted to inpatient rehabilitation post stroke. Interventions: Patient-Directed Activity Program (PDAP) or control (usual care only). Both groups underwent control (three hours of therapy/day), while PDAP participants were prescribed two additional 30-minute activity sessions/day. Main measures: Outcomes (Stroke Rehabilitation Assessment of Movement Measure, Functional Independence Measure, balance, physical activity, Stroke Impact Scale) were collected at admission and discharge from inpatient rehabilitation and three-month follow-up. Results: Seventy-three patients (PDAP ( n  = 37); control ( n  = 36)) were included in the primary analysis. Patients in PDAP completed a total of 23.1 ± 16.5 sessions (10.7 ± 8.5 upper extremity; 12.4 ± 8.6 lower extremity) during inpatient rehabilitation. No differences were observed between groups at discharge in functional measures. PDAP completed significantly more steps/day (PDAP = 657.70 ± 655.82, control = 396.17 ± 419.65; P  = 0.022). The Stroke Impact Scale showed significantly better memory and thinking (PDAP = 86.2 ± 11.4, control = 80.8 ± 16.7; P  = 0.049), communication (PDAP = 93.6 ± 8.3, control = 89.6 ± 12.4; P  = 0.042), mobility (PDAP = 62.2 ± 22.5, control = 53.8 ± 21.8; P  = 0.038), and overall recovery from stroke (PDAP = 62.1 ± 19.1, control = 52.2 ± 18.7; P  = 0.038) for PDAP compared to control. At three months post discharge, PDAP ( n  = 11) completed significantly greater physical activity ( P  = 0.014; 3586.5 ± 3468.5 steps/day) compared to control ( n  = 10; 1760.9 ± 2346.3 steps/day). Conclusion: Functional outcome improvement was comparable between groups; however, PDAP participants completed more steps and perceived greater recovery.